2022
DOI: 10.3389/fpubh.2022.890420
|View full text |Cite
|
Sign up to set email alerts
|

Salivary miRNA Expression in Children With Persistent Post-concussive Symptoms

Abstract: BackgroundUp to one-third of concussed children develop persistent post-concussive symptoms (PPCS). The identification of biomarkers such as salivary miRNAs that detect concussed children at increased risk of PPCS has received growing attention in recent years. However, whether and how salivary miRNA expression levels differ over time between concussed children with and without PPCS is unknown.AimTo identify salivary MicroRNAs (miRNAs) whose expression levels differ over time post-concussion in children with v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…Only one study assessed multiple biomarkers 10. The most commonly studied biomarker was salivary microRNA which was examined in 11 studies 11–21. Cortisol was assessed in four studies 10 22–24.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only one study assessed multiple biomarkers 10. The most commonly studied biomarker was salivary microRNA which was examined in 11 studies 11–21. Cortisol was assessed in four studies 10 22–24.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies specifically the paediatric population (≤18 years old) 10 21 25 27 28. However, 82.8% of studies included paediatric subjects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A subset of salivary and serum miRNAs predicted the likelihood of a TBI and demonstrated quantitative associations with head impacts and cognitive and balance measures in a group of twenty-four martial arts fighters, and salivary miRNAs demonstrated far more utility [ 59 ]. Miller et al [ 60 ] identified thirteen salivary miRNAs with significantly various levels in children with a history of mild TBI and with or without PPCS.…”
Section: Salivary Biomarkersmentioning
confidence: 99%
“…Expression studies of miRNAs from human saliva have been increasing over the past decade, across a number of clinical disciplines. Notably, high powered cohort studies identify predictive miRNAs for of autism spectrum disorder [ 4 , 16 , 17 ], traumatic brain injury [ 18 , 19 , 20 , 21 ] endometriosis [ 22 ], and a variety of cancers [ 23 , 24 , 25 ]. Other recent studies include the prediction of alcohol use disorder [ 26 , 27 ], Parkinson’s Disease [ 28 , 29 ], and malignant pleural effusion [ 30 ].…”
Section: Introductionmentioning
confidence: 99%